Natural variation in fatty acid composition of diverse Vietnamese rice germplasm - Phuong Nga, Mai Thi; Thuy Linh, Nguyen Thi; Anh Nguyet, Tran Thi; Hong Ngoc, Ngo Thi; Quynh Anh, Chu Thi; Mai Huong, To Thi (Vietnam Journal of Biotechnology, 2023)
Despite the advantages of rice bran oil in terms of nutrition and healthcare, the knowledge of its fatty acid composition was still limited. A panel of 100 rice varieties generated from the different ecosystems of Vietnam had been used in our study to investigate their fatty acid profile. Using the modern Gas Chromatography-Mass Spectrometry method, five main fatty acids in our rice bran were discovered including myristic (14:0), palmitic (C16:0), stearic (C18:0), oleic (C18:1) and linoleic (C18:2) acids, in which the fatty acids profile were different and specific for each variety. Among the five fatty acids, the essential linoleic fatty acid content was the highest whereas the myristic acid had the lowest content. The genotype G31 (NEP CAM) had been found with the highest linoleic fatty acid content (43.5%) which could be considered a good source of food and potential for breeding. In this study, we also determined the correlation between the five fatty acids (FAs) content in each rice variety and in comparison with different genotypes. A strong positive correlation between palmitic acid content and the ratio of saturated and unsaturated fatty acid (R = 0.98) was obtained in this study. The ratio of saturated and unsaturated fatty acid in Japonica genotypes is lower than Indica (p < 0.001), indicating that Japonica genotypes have more favorable unsaturated FA. Our study’s results may have great importance in contributing to future breeding programs to improve fatty acid components in our Vietnamese rice.